2009
DOI: 10.1002/ajpa.21227
|View full text |Cite
|
Sign up to set email alerts
|

Oval in males and triangular in females? A quantitative evaluation of sexual dimorphism in the human obturator foramen

Abstract: Among the numerous pelvic traits presenting sex differences, the obturator foramen is classically described as being oval in males and triangular in females. However, no demonstrations or detailed studies seem available in the literature. The purpose of this work was to study quantitatively this trait using Fourier analysis, because this methodological approach is particularly well adapted for discrimination between different simple shapes. Using this approach, an outline can be characterized by a series of ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…They also suggested that the experience of the observer was important, noting differences in accuracy of up to 14% between experienced and inexperienced observers. The article is cited by numerous forensic and bioarchaeological studies, including widely cited laboratory and field manuals, as indicative evidence that the accuracy of the Phenice method is variable depending on sample ancestry and the experience of the observer (e.g., Sutherland and Suchey, ; Tague, ; Rogers and Saunders, ; Lou, ; Cox and Mays, ; Bruzek, ; Scheuer, ; Ubelaker and Volk, ; Albanese et al, ; Listi and Bassett, ; Albanese et al, ; Cardoso and Saunders, ; Gonzalez et al, ; Bierry et al, ; Bytheway and Ross, ; White et al, ).…”
Section: Four Models Using the Maclaughlin And Bruce () Resultsmentioning
confidence: 99%
“…They also suggested that the experience of the observer was important, noting differences in accuracy of up to 14% between experienced and inexperienced observers. The article is cited by numerous forensic and bioarchaeological studies, including widely cited laboratory and field manuals, as indicative evidence that the accuracy of the Phenice method is variable depending on sample ancestry and the experience of the observer (e.g., Sutherland and Suchey, ; Tague, ; Rogers and Saunders, ; Lou, ; Cox and Mays, ; Bruzek, ; Scheuer, ; Ubelaker and Volk, ; Albanese et al, ; Listi and Bassett, ; Albanese et al, ; Cardoso and Saunders, ; Gonzalez et al, ; Bierry et al, ; Bytheway and Ross, ; White et al, ).…”
Section: Four Models Using the Maclaughlin And Bruce () Resultsmentioning
confidence: 99%
“…Thirdly, although FSA is a methodological approach particularly well adapted to discrimination between different simple shapes (Bierry et al., ), it too showed a low rate of accuracy in classification according to sex.…”
Section: Discussionmentioning
confidence: 99%
“…Fourier shape analysis (FSA) is a technique for generating from a poor outline, a set of shape‐representative variables suitable for use in statistical comparisons between samples. It has been applied to many bones, but there are few papers dealing with foramen analysis (Bierry et al., ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations